2015
DOI: 10.3390/ijms161226194
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Virulence Regulation by Small Noncoding RNAs in Low GC Gram-Positive Pathogens

Abstract: The discovery of small noncoding regulatory RNAs (sRNAs) in bacteria has grown tremendously recently, giving new insights into gene regulation. The implementation of computational analysis and RNA sequencing has provided new tools to discover and analyze potential sRNAs. Small regulatory RNAs that act by base-pairing to target mRNAs have been found to be ubiquitous and are the most abundant class of post-transcriptional regulators in bacteria. The majority of sRNA studies has been limited to E. coli and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 92 publications
(189 reference statements)
1
13
0
Order By: Relevance
“…Surprisingly, inactivation of Hfq, an sRNA chaperone well described in Gram-negative bacteria, did not yield any alterations in the levels of transcripts of three analyzed sRNAs (i.e., teg49, teg23, and teg35). This finding indicated that Hfq does not have a major role in stabilizing sRNA in S. aureus, consistent with other reports of Gram-positive bacteria (23).…”
Section: Figsupporting
confidence: 92%
See 3 more Smart Citations
“…Surprisingly, inactivation of Hfq, an sRNA chaperone well described in Gram-negative bacteria, did not yield any alterations in the levels of transcripts of three analyzed sRNAs (i.e., teg49, teg23, and teg35). This finding indicated that Hfq does not have a major role in stabilizing sRNA in S. aureus, consistent with other reports of Gram-positive bacteria (23).…”
Section: Figsupporting
confidence: 92%
“…The discovery of sRNAs in bacteria in the last 2 decades has provided new insights into gene regulation. sRNAs have been found to be ubiquitous and represent the most abundant class of posttranscriptional regulators in prokaryotes (21)(22)(23). Most of the sRNAs act by base pairing with target mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Premature transcription termination (PTT) within 5' untranslated regions were recently shown to be widespread events in the Gram-positive bacteria B. subtilis, Listeria monocytogenes and Enterococcus faecalis (Dar et al, 2016 (Bohn et al, 2010;Rochat et al, 2018) and also to promote biofilm formation in Staphylococcus epidermidis by supporting extracellular DNA release and the production of polysaccharideintercellular adhesin (PIA) (Schoenfelder et al, 2019). However, the function of Hfq in facilitating the interactions between sRNA regulators and their target mRNAs in Gram-positive bacteria remains elusive, since most of the known sRNAs seem to exert their regulatory activity independent of this global RNA-binding protein (Pitman and Cho, 2015).…”
Section: Discovery Of Novel Regulatory Functions Located In 5' Utrsmentioning
confidence: 99%